Una nueva visión de la enseñanza: el método integral en la enseñanza-aprendizaje del español como lengua extranjera en adultos - Cámero Room, Araceli (2011)
The present article presents the integral method as a very interesting alternative in the teaching and learning process of a foreign language far adu lt s. lt has also the purpose to focus on the grammatical explanation of the fareign language in such process, which leads to center on the adult student, which variables such as: age, social culture, preferences and experiences are taken into account with a vital relevance on the development of the learning -teaching process of aforeign language.